Penerapan Zakat Sebagai Pengurang Penghasilan Kena Pajak Orang Pribadi Pada BAZNAS Kab.Bulukumba: Penerapan Zakat Sebagai Pengurang Penghasilan Kena Pajak Orang Pribadi Pada BAZNAS Kab.Bulukumba - Muchriana Muchran; Ismawati Ismawati; Abdul Khaliq; Wahyuni Wahyuni (Al-Buhuts, 2022)
This study aims to determine the application of zakat as a deduction from individual taxable income in the National Amil Zakat Agency (BAZNAS) Bulukumba Regency. The research method used is field research, with a descriptive approach. That is describing zakat as a tax deduction. Sources are taken from various references related to the topic of the problem, namely from agency records, journals, laws and so on. The results of the study conclude that Zakat can be used as a Taxable Income Deduction if the muzakki pays zakat to BAZNAS, then BAZNAS issues the Zakat Deposit proof which later the Zakat Deposit (BZS) proof can be used as a taxable income deduction (PKP) on income tax by attaching it on the annual tax return. The inhibiting factors in the application of zakat as a deduction from taxable income are the low awareness of paying zakat, the public is not yet interested in zakat institutions, the limited number of BAZNAS or Laz authorized by the government, the reluctance of the community to include Evidence of Zakat Deposit (BZS) in the Annual SPT and the lack of socialization of zakat. as a deduction for Income Tax for Individual Taxpayers